Characterization of placenta‐specific microRNAs in fetal growth restriction pregnancy. (27th January 2013) - Higashijima, Ai; Miura, Kiyonori; Mishima, Hiroyuki; Kinoshita, Akira; Jo, Ozora; Abe, Shuhei; Hasegawa, Yuri; Miura, Shoko; Yamasaki, Kentaro; Yoshida, Atsushi; Yoshiura, Koh‐ichiro; Masuzaki, Hideaki
ABSTRACT Objective The aim of this study was to characterize placenta‐specific microRNAs in fetal growth restriction (FGR) pregnancy. Method Placenta‐specific miRNAs were identified by next‐generation sequencing analysis. Subsequently, quantitative real‐time reverse‐transcription polymerase chain reaction was used to identify FGR placenta‐specific miRNAs whose level of expression was significantly decreased in FGR placenta (n = 45) compared with uncomplicated placenta (n = 50). FGR pregnancy‐associated, placenta‐specific microRNAs were identified in maternal plasma after delivery at significantly decreased concentrations, and their circulating levels in maternal plasma was compared between FGR pregnancies (n = 10) and uncomplicated pregnancies (n = 10). Results Out of the ten placenta‐specific microRNAs that we identified, seven placenta‐specific microRNAs (hsa‐miR‐518b, hsa‐miR‐1323, hsa‐miR‐516b, hsa‐miR‐515‐5p, hsa‐miR‐520h, hsa‐miR‐519d, and hsa‐miR‐526b) from the chromosome 19 microRNA cluster were identified as FGR placenta‐specific microRNAs. Four FGR placenta‐specific microRNAs (hsa‐miR‐518b, hsa‐miR‐1323, hsa‐miR‐520h, and hsa‐miR‐519d) were confirmed as FGR pregnancy‐associated, placenta‐specific miRNAs, but their circulating levels in maternal plasma showed no significant differences between FGR pregnancy and uncomplicated pregnancy. Conclusion Our data suggest that reduced expression in placenta of certain FGR placenta‐specific miRNAs is associated with FGR and that the discrepancy between expression in FGR placenta and their circulating levels in maternal plasma will be crucial to understanding how placenta‐specific microRNAs are released into the maternal circulation. © 2013 John Wiley & Sons, Ltd.